The Influence of Practice Method on Volleyball Normal Smash Ability Viewed From Leg Muscle Power - Anggara Harini; Kristiyanto Agus; Siswandari Siswandari (Kazimierz Wielki University, 2018)
Background, students sport achievement in volleyball achievement development activity is not maximum nowadays. This can be proved from volleyball competition result that had been followed by them have not shown satisfying result.This research means to (1) Examine the difference of the influence of part whole part and whole part whole practice method on volleyball achievement development student, (2) Examine the difference of leg muscle on normal smash of volleyball achievement development student, (3) Examine the influence of interaction between practice method and leg muscle power to normal smash ability of volleyball achievement development student. This research is experimental research that means to compare two different treatments to research subject. The research used experimental method with 2x2 factorial design. The sample are 32 using probability sampling technique. Independent variable is part whole part and whole part whole practice method. Attributive variable is high leg muscle power and low leg muscle power. Dependent variable is volleyball smash ability. Data collection techniques in this research are pretest and posttest. Data analysis technique used is Varians analysis (ANAVA). Population in this research is student in volleyball achievement development activity Sebelas Maret University. The Result of this research that student group is given whole part whole practice method have better result compared with student group that is given part whole part practice one (104,37 ˃ 81,75) toward volleyball smash result. In student group having high leg muscle power has better result compared with student group having low leg muscle (112.31>70.87) toward volleyball smash result. There is interaction between practice method and leg muscle power toward volleyball smash result. The Conclusions of this research, there is different influence between volleyball smash practice using part whole part and whole part whole practice method toward volleyball smash result. Furthermore, there is different influence between sample group with high level of leg muscle power and low level of leg muscle power toward volleyball smash result. Last, there is interaction influence between leg muscle power and practice method to volleyball smash result.